TRANSPARANSI PEMERINTAH DAN KINERJA DAERAH DALAM MEMBANGUN KEPERCAYAAN POLITIK MASYARAKAT - Asep Somanteri (Sawala Cendikia : Jurnal Penelitian Multidisiplin, 2025)
Political trust is a vital indicator of the quality of a democratic system, reflecting the extent to which the public believes that government institutions can function effectively, responsively, and accountably. This study aims to empirically analyze the influence of local government performance and government transparency on public political trust in Sindangbarang District, Cianjur Regency. The research employs a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS 4.0 software. Data were collected through online questionnaires using a Likert scale from 300 respondents who are residents of Sindangbarang District. The results of the study indicate that local government performance has a positive and significant influence on public political trust (t-statistic 9.928; p-value 0.000), with a path coefficient of 0.456. Furthermore, government transparency also demonstrates a significant positive influence on political trust, showing a stronger impact than the performance variable (t-statistic 11.547; p-value 0.000; path coefficient 0.525). The research model exhibits very high predictive power with an R-Square value of 94.2%, meaning these two variables explain the vast majority of variations in public political trust in the region. Additionally, the Goodness of Fit test resulted in an SRMR value of 0.042, indicating an excellent model fit. The study concludes that the synergy between effective public service performance and information openness is a fundamental pillar for achieving good governance and strengthening political legitimacy at the local level